Lexical Diversity in Chili Farming in Kemurang Village, Brebes: A Semantic Study - Chintia Nurrokhmah Romadhon; Nur Fateah; Ermi Dyah Kurnia (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
The role of language in people's lives is very important as a medium for passing on knowledge and traditions between generations. One manifestation of this linguistic richness is seen in the use of traditional lexicons in agricultural activities that are closely related to Javanese society, including the people of Kemurang Village, Brebes Regency, who rely on chili farming as their main livelihood. Semantic studies on agricultural lexicons are crucial in documenting and preserving traditional knowledge that is threatened with extinction due to modernization. This study aims to describe the agricultural lexicon of chili planting and describe the meaning of agricultural lexicons in the process of chili planting in Kemurang Village, Brebes Regency. To explore the problem under study, the researcher in this case uses the study of word class theory by Chaer (2012) as well as lexical and cultural semantic studies. The study uses a qualitative descriptive method with a semantic approach. The data are in the form of oral speech in the Ngapak dialect of Javanese used by farmers in the process of cultivating chili plants. The results of the study found that the chili farming process in Kemurang Village contained 48 lexicons consisting of noun, verb, and adjective categories, and each lexicon has lexical and cultural meaning . These lexicons are grouped into seven categories, namely: (1) the process of cultivating chili plants (2) the process of land preparation (3) naming types of chili plants (4) the process of sowing chili plants (5) the process of maintaining chili plants (6) mentioning the condition of chili plants, and finally (7) mentioning the harvest period of chili plants. This finding shows that the agricultural lexicon not only enriches agricultural technical knowledge, but also represents the cultural identity of the Kemurang Village community and has the potential to support the preservation of regional languages, especially the Ngapak dialect of Javanese.